IMPLEMENTASI PELAYANAN PUBLIK DI DINAS PARIWISATA DI KOTA MANADO - MONINTJA, CHRISTOPHER; TULUSAN, FEMMY; PLANGITEN, NOVVA (Sam Ratulangi University, 2017)
Abstract: Implementation of Public Service is all services organized by public service providers as an effort to meet theneeds of service recipients and implementers of legislation. Public service is basically about the vast aspects of life. In thelife of the state, the government has the function of providing various public services required by the community. One thingthat until now is often still a problem in the relationship between the people and the government in the region is in the fieldof public services, especially in terms of the quality or quality of service government apparatus to the community.Tourism is currently being intensively incentive in the city of Manado. Lots of local and foreign tourists visiting the city ofManado. But with the level of service is said to be less than the relevant Office to make the process of tourism is not goingwell.In this research used qualitative research method, so the researcher will not specify the research only based on researchvariable, but the whole social situation examined covering aspect of place, actors and activity that interact synergistically.The result of the research shows that the lack of public service available in the Manado City Tourism Office makes thetourism process less good. With the level of human resources that have not qualified with the limitations of foreign languageskills make the tourists, especially foreign tourists feel uncomfortable. The tourism program created by the governmentitself has not been fully felt directly by the community. Lack of socialization of the existence of tourism programs from thegovernment to make people less aware of the importance of existing tourism.Keywords: Implementation of Public Service, Tourism, Qualitative.